Honduras: The impact of COVID-19 and preliminary implications: Interim report - Díaz-Bonilla, Eugenio; Piñeiro, Valeria; Laborde Debucquet, David (International Food Policy Research Institute, 2021)
Due to the global pandemic generated by the COVID-19 the government of Honduras declared “state of emergency” in Feburay (“Estado de Emergencia en el Territorio Nacional a través del Decreto Ejecutivo Número PCM- 005-2020, 10 de febrero 2020). The country suffered the first confirmed COVID-19 case on March 12th, 2020. The first death was registered on March 26th. This short covers the following topics until the time of this report. First, it shows the evolution of the pandemic, using different indicators. Second, it summarizes the main responses and costs and financing implied. Third, it shows some actual impacts with available data. Fourth, the modeling framework for the simulations is briefly presented. Fifth, it simulates different scenarios for the evolution of the Honduras’ economy until year 2022. A final section discusses some preliminary considerations. Subsequent reports will update the information of this document and sharpen de conclusions.